Design and Development of a Garlic Dryer (Allium sativum L.) with the Addition of Parafin as a Heat Storage Medium - Afdhalul Ahmar; Moh Haifan; M. Arief Yahdi; Lalu Muh Fathul Aziz Al Azhari (The University of Lampung, 2025)
Garlic is an important commodity as a basic spice for various dishes with several health benefits such as lowering blood pressure and improving immune system. Fresh garlic has a high moisture content of 60.9-67.8%, making it highly susceptible to microbial spoilage. The drying process is a critical post-harvest step for garlic that significantly influences product quality and shelf life. This study aims to design a garlic drying system enhanced with solar collector and parafin as a thermal storage medium. Parafin provides heat during periods of low sunlight, allowing continuous drying. The methodology includes the design, construction, and testing of the drying equipment. Functional tests demonstrate effective operation of the dryer components. The results of testing the dryer for drying garlic were able to reduce the water content of garlic from 60% wb to 11.2% wb for 8 h of drying. The use of paraffin has proven to be effective in helping to maintain the drying temperature, especially when the intensity of sunlight is reduced, so that the drying process remains optimal.